Structural Analysis of Opinion Essays by Second-year EFL Teacher Training Students - Lkhagva, Enkhbayar (Mongolian Journal of Humanities and Social Sciences, 2024)
This study examines the structural analysis of opinion essays written by second-year EFL teacher training students. In an era where written communication in second languages (L2) is indispensable across various fields, the demand for writing skills has become increasingly central to school and university curricula. Among different types of academic essays, mastering the genre of opinion essays is essential for students. This study assesses how effectively second-year EFL teacher-training students have learned to write opinion essays. Following a qualitative approach, opinion essays written by 40 undergraduate students were analyzed. The findings indicate that most students could effectively structure their opinion essays according to the prescribed format. Students successfully provided general statements followed by a thesis statement in the introduction, developed well-structured body paragraphs with clear topic sentences and supporting details, and offered practical conclusions. The study highlights the importance of teaching academic writing skills and provides educators with insights on effectively teaching opinion essay writing to EFL students. This research contributes to understanding how second-year EFL teachers train students to develop their skills in writing opinion essays. The findings underscore the importance of structured academic writing instruction and offer valuable insights for educators seeking to enhance the teaching of opinion essay writing to EFL students. Англи хэлний багшийн 2-р ангийн оюутнуудын үзэл бодлоо илэрхийлсэн эссэний бүтцэд хийсэн дүн шинжилгээ Хураангуй: Оюутнууд үзэл бодлоо илэрхийлсэн эссэг бичиж сурах нь зайлшгүй байна. Тус судалгаа нь Англи хэлний багшийн 2-р ангийн оюутнууд үзэл бодлоо илэрхийлсэн эссэг бүтцийн дагуу хэр үр дүнтэй бичиж сурч байгааг үнэлэх зорилготой. Тус судалгаа нь эссэнд бүтцийн анализ хийх чанарын аргыг ашиглаж англи хэлний багшийн 2-р ангийн 40 оюутны 70 эссэнд бүтцийн дүн шинжилгээ хийж үзэхэд ихэнх оюутнууд (70%) бүтцийн дагуу үзэл бодлоо илэрхийлсэн эссэг бичиж сурсан байна. Тус судалгаанд цөөн тооны жишээ эссэг харуулсан. Дийлэнх оюутнууд эссэний удиртгал цогцолборт сэдвийн талаарх ерөнхий мэдээлэл, гол санаа агуулсан мэдээллийг хангалттай үнэлгээтэй гаргасан байна. Мөн дэлгэрүүлэгч цогцолборт хөтөч санаа түүнийг дэмжсэн жишээ өгүүлбэрүүдийг мөн хангалттай үнэлгээтэй бичсэн байна. Дүгнэлт өгүүлбэрийг мөн заасны дагуу 2 аргаар бичиж сурсан байна. Үүнд гол санааг өөрийн үгээр илэрхийлж бичихээс гадна хөтөч санааг дурдаж бичсэн байна. Түлхүүр үг: удиртгал цогцолбор, дэлгэрүүлэгч цогцолбор, дүгнэлт цогцолбор